Heidegger's claim "Carl Schmitt thinks as a Liberal". Issue 3 (2nd July 2016) - Hemming, Laurence Paul
Abstract : This paper examines Heidegger's critique of Carl Schmitt during the Nazi period, focusing on Heidegger's notes for seminars on Hegel's Philosophy of Right . Taking up Heidegger's and Schmitt's critique of Hegel, Heidegger argues that the friend/enemy distinction Schmitt makes is still grounded in a humanistic liberalism, and so in the very Hegelian subjectivity that Schmitt claims to reject. Heidegger then turns to the question of dikē, and shows how there is a more originary grounding for the polis and the state in a concept Heidegger develops from his analysis of Anaximander. Grounding this is the question which concerns which God (or which goddess) grounds any past, present, or future "political theology".